The Transformation of Affordable Housing Provision Policy in Johor - Ngadiman, Norshafadila; Husin, Khadijah (School of Social Sciences, USM, 2017)
State governments are given flexibility in forming housing policies based on demand and suitability of locations. Johor Housing Policy was formed in 1997 and re-enacted in 2012 branded as Johor Affordable Housing Policy (Dasar Perumahan Rakyat Johor). Changes of a public policy are a condition that requires a legal or policy reviewed to monitor its effectiveness from time to time. Johor housing policy transformation performed in order to overcome the problem of excess low-cost houses because of several factors such as invalid target group of buyer, non-strategic location and unsatisfied design of housing. Affordability housing issues in Johor is a reflection of missmatch between the supply and demand of housing due to net enhancement of households. In addition, the increase rate of household income is slower than the house price. Therefore, state authorities evaluate the previous housing policy to tackle affordability issues to ensure people of Johor can own a house per family by year 2020. This study will identify the transformation of Johor Affordable Housing Policy by reviewing Johor’s background affordability to own a house and how the changes of housing policies could solve the problem of housing ownership. The compulsory provision of forty percent of affordable housing in each housing project construction shows that the housing policy changes made turned out to bring positive impact to the ownership of affordable houses in Johor.